2014
DOI: 10.1093/hmg/ddu150
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty

Abstract: Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 71 publications
2
61
1
Order By: Relevance
“…Specific gene loci, LIN28B on chromosome 6 is associated with earlier signs of sexual maturation and tempo of growth in both genders 22 . MKL2 on chromosome 16 is associated with menarcheal timing in girls and pubertal timing in boys, indicating common loci for initiation of puberty between the genders 23. Loci associated with increasing body mass index were also associated with earlier puberty in girls, and either earlier or later pubertal timing in boys, consistent with epidemiological data in body composition and pubertal timing 23…”
Section: Factors Controlling the Timing Of Pubertysupporting
confidence: 78%
“…Specific gene loci, LIN28B on chromosome 6 is associated with earlier signs of sexual maturation and tempo of growth in both genders 22 . MKL2 on chromosome 16 is associated with menarcheal timing in girls and pubertal timing in boys, indicating common loci for initiation of puberty between the genders 23. Loci associated with increasing body mass index were also associated with earlier puberty in girls, and either earlier or later pubertal timing in boys, consistent with epidemiological data in body composition and pubertal timing 23…”
Section: Factors Controlling the Timing Of Pubertysupporting
confidence: 78%
“…Moreover, even in the absence of genetic variants with sex-specific effects, the study of the genes and pathways identified by GWAS provides an opportunity to uncover new factors that contribute to male-female differences in traits such as growth and the timing of puberty since, for example, these genes and pathways may be modulated by differential sex-steroid exposures or epigenetic mechanisms. Sex-specific effects of the Lin28a/Lin28b/let-7 axis have already been identified in growth patterns in mice and humans (Cousminer, et al 2014; Leinonen et al 2012; Lettre et al 2008; Ong et al 2011; Shinoda et al 2013b; Widen et al 2010). By verifying previously published sex differences in the regulation of body weight in a second animal facility and expanding these observations to include sex-specific effects on pubertal timing, we provide further evidence that the Lin28a/Lin28b/let-7 axis can exert sex-specific effects in mice.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship of BMI and onset of puberty may be mediated by several factors, such as leptin and kisspeptin, changes in the bioavailability of sex steroids, and environmental exposures for example to endocrine-disrupting chemicals. Recently there have been genome-wide meta-analyses examining onset of puberty and anthropometric traits, and they may provide insight into the relationships of BMI, height velocity, and pubertal timing [85, 86]. Newer fields of investigation include examination of epigenetic modification [87].…”
Section: Obesity and Pubertal Onset And Progressionmentioning
confidence: 99%